The effect of multi-wall carbon nanotubes on sex hormone levels and ovarian tissue in female Wistar rats - Narges Vaziri-Katehshori (Fiyz̤, 2018)
Background: Due to the application of carbon nanotubes in biological fields and the possibility of their toxic effects, this study was conducted to examine the toxic effect of multi-wall carbon nanotubes on ovaries in rats. Materials and Methods: In this experimental study, 50 rats were studied as follows: control group received normal saline, and experimental groups received the concentrations of 2.5, 5, 10, 20 mg/kg of multi-wall carbon nanotubes functionalized with the carboxylic group in 8 steps intraperitoneally. Blood samples were collected in two phases (one day and 20 days after the last injection) and the serum hormone levels of FSH, LH, estrogen, and progesterone and also the amount of malondialdehyde were measured. In addition, the tissue sections of ovary were stained by hematoxylin-eosin and studied. Results: The results of the first stage showed a significant reduction in all hormones in all concentrations in the experimental group compared to the control group. In the second stage, the level of FSH increased significantly in exposure to 10 and 20mg/kg concentrations of nanotubes and the estrogen level increased by 20mg/kg concentration of nanotubes, but the LH and progesterone hormones showed no significant change compared to the control group. There was no significant difference in the mean weight of the rats and the amount of malondialdehyde during the experiment. The histological results showed degradation of the granular layer, absence of corpus luteum and non-oocyte follicles in exposure to 10 and 20mg/kg concentrations of carbon nanotubes. Conclusion: It seems that carbon nanotubes, along with probable accumulation in the ovary, with the effect of oxidative stress, affect the level of sex hormones and cause disorders in the ovarian tissue.